1985
DOI: 10.1007/bf00017973
|View full text |Cite
|
Sign up to set email alerts
|

On the measurement of dynamic fracture toughnesses ? a review of recent work

Abstract: The influence of dynamic effects on test procedures for measuring the crack arrest toughness and the impact fracture toughness is analyzed. It is shown that these dynamic effects can be significant: For cracks at arrest the stress condition is still dynamic and not static although the crack velocity has become zero. Dynamic effects become small only for small crack velocities or small crack jumps or for specially designed specimens. It is shown that the stress intensity factor history for cracks under impact l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(48 citation statements)
references
References 12 publications
3
44
0
1
Order By: Relevance
“…It was shown (Kalthoff, 1985) that the dynamic effects at the crack tip were significantly smaller than the load measured at the striker contact point. This means that expensive instrumentation of the specimen was necessary and the load-time trace from the crack-tip strain gauge must be used for high rate tests (Carolan et al, 2010).…”
Section: High-rate Testsmentioning
confidence: 97%
“…It was shown (Kalthoff, 1985) that the dynamic effects at the crack tip were significantly smaller than the load measured at the striker contact point. This means that expensive instrumentation of the specimen was necessary and the load-time trace from the crack-tip strain gauge must be used for high rate tests (Carolan et al, 2010).…”
Section: High-rate Testsmentioning
confidence: 97%
“…[20] showed that the dynamic effects at the crack tip were significantly smaller than the load measured at the striker contact point. It follows then, that there exists a unique relationship between the dynamic fracture toughness of the material and the time to fracture initiation.…”
Section: High Rate Testsmentioning
confidence: 95%
“…However, the Hopkinson bar loading experimental technique that can be used to study various dynamic fracture properties of materials under a stress-intensity factor rate ∼ 10 6 MPa m 1/2 s −1 are still being developed [2][3][4][5][6][7][8]. The one-bar (one incident loading bar)/three-point bending (3PB) impact setup [9][10][11][12][13][14][15][16] is currently the most popular setup used to determine the dynamic fracture toughness of materials under stress wave loading, since this loading configuration has some advantages: (1) the loading rate acquired in such one-bar/3PB loaded fracture test is higher than that in Charpy impact test [17][18][19][20][21][22][23][24][25][26]; (2) the dynamic response of fracture specimen can be determined via *Corresponding author: tel. : +86 451 82569890; e-mail address: fengchunjiang@hrbeu.edu.cn strain signals recorded by the strain gauges mounted on the loading bar; and (3) a relatively large fracture specimen can be used for measuring the valid plane strain fracture toughness [1,[27][28].…”
Section: Introductionmentioning
confidence: 99%